Analisis Frase dalam Berita RiauPos.co - Ayunilarasandi, Nabilarosa; S., Ermawati (UIR PRESS, 2021)
Phrases are grammatical units consisting of two or more words that occupy a sentence function. The problems examined in this study are (1) What are the eccentric phrases contained in Berita RiauPos.co? (2) What are the endocentric phrases contained in Berita RiauPos.co? (3) What is the coordinating phrase contained in Berita RiauPos.co? (4) What are the positive phrases contained in Berita RiauPos.co? The purpose of this study is to describe, analyze, conclude and interpret exocentric, endocentric, coordinative and appositive phrases contained in Berita RiauPos.co. The theory used to analyze the problem of this research is the theory of Chaer (2012). The research method used in this research is a descriptive method with a qualitative approach. This type of research includes library research (library research). The results and conclusions of this study are (1) The eccentric phrases found in RiauPos.co include the ecocentric directive phrases in the city of Pekanbaru, because the two elements of these phrases do not have the same distribution as their components. Both with prepositions and with their central elements. The proposed phrases include non-directive ecocentric phrases, because non-directive exocentric phrases are articulus, while the central elements are words or groups of words that are categorized as verbs. (2) The endocentric phrases found in RiauPos.co include new students because one of the elements can replace their general position. (3) Coordinating phrases found in RiauPos.co include students and students of these phrases that have equivalence or declare something equivalent. (4) The positive phrases found on RiauPos.co include the Rector of Lancang Kuning University (Unilak), Dr. Junaidi, which refer to each other. All the sentences contained in Berita RiauPos.co, up to 106 sentence data were obtained.